Albumin Identification in Catfish ( Clarias sp ) Using Spectrophotometry UV-VIs - Perti Fitriani; Davit Nugraha (LPPM STIKes Muhammadiyah Ciamis, 2023)
Albumin is a simple protein with globular protein molecules. Albumin is water soluble and can be coagulated with heat. Albumin solution in water can be precipitated by adding ammonium sulfate until saturated. Albumin functions to regulate the osmotic pressure in the blood, maintain the presence of water in the blood plasma so that it can maintain the volume of blood in the body and as a means of transportation and transportation. Catfish contains 15.6 grams of high-quality protein in each fish so that it can meet the needs of the amino acids needed by the body. The high-quality protein in catfish helps the body build lean brain mass and the protein content in catfish also helps increase the effectiveness of immune function. The purpose of this study was to determine albumin levels in catfish by extracting catfish meat using the oven method and determining the maximum albumin wavelength. In the identification test with the heating method and UV-Vis spectrophotometry test. This research method uses the experimental method. The extraction results were then heated in an oven to observe coagulation and determine the wavelength using UV-Vis spectrophotometry using Bovine Serum Albumin (BSA) as a reference solution and Bromocressol green as a reagent. The conclusion of this study is that catfish meat extract was coagulated using the oven method and maximum absorption was obtained at a wavelength of 625 nm using UV-Vis spectrophotometry.